2015
DOI: 10.1371/journal.pone.0131567
|View full text |Cite|
|
Sign up to set email alerts
|

Introgression of the SbASR-1 Gene Cloned from a Halophyte Salicornia brachiata Enhances Salinity and Drought Endurance in Transgenic Groundnut (Arachis hypogaea) and Acts as a Transcription Factor

Abstract: The SbASR-1 gene, cloned from a halophyte Salicornia brachiata, encodes a plant-specific hydrophilic and stress responsive protein. The genome of S. brachiata has two paralogs of the SbASR-1 gene (2549 bp), which is comprised of a single intron of 1611 bp, the largest intron of the  abscisic acid stress ripening [ASR] gene family yet reported. In silico analysis of the 843-bp putative promoter revealed the presence of ABA, biotic stress, dehydration, phytohormone, salinity, and sugar responsive cis-regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 78 publications
6
65
0
Order By: Relevance
“…It has been reported that TaASR1 and SbASR1 induce the transcription of ROS scavenger-associated genes and reduce the accumulation of ROS (Hu et al, 2013; Tiwari et al, 2015). To analyze the role of SiASR4 in ROS scavenging in transgenic Arabidopsis , 3-week-old Col-0 and transgenic Arabidopsis grown in pots were not watered and were treated with salt for 6 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that TaASR1 and SbASR1 induce the transcription of ROS scavenger-associated genes and reduce the accumulation of ROS (Hu et al, 2013; Tiwari et al, 2015). To analyze the role of SiASR4 in ROS scavenging in transgenic Arabidopsis , 3-week-old Col-0 and transgenic Arabidopsis grown in pots were not watered and were treated with salt for 6 days, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The loblolly pine ASR gene lp3 is induced by water deficit stress mediated by ABA (Padmanabhan et al, 1997). A Salicornia brachiata ASR gene, SbASR1 , enhances drought and high-salinity tolerance in transgenic groundnut (Tiwari et al, 2015). In foxtail millet, six ASR genes were identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-myristoylation facilitates protein folding and improves their thermostability (de-Jonge HR et al 2000). N-myristoylation was also found to be important for proper functioning of Arabidopsis gene, SOS3 ( Salt overly sensitive 3 ) having important role in plant salt tolerance (Ishitani et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A bacterial mtlD gene encoding mannitol 1-phosphate dehydrogenase when expressed in groundnut cultivar GG20 under a constitutive promoter CaMV35s conferred drought tolerance through accumulation of mannitol (Bhauso et al, 2014). The genes from Salicornia brachiata, ascorbate peroxidase ( SbAPX ), and abscisic acid stress ripening ( SbASR ) genes when expressed in groundnut displayed salt and drought stress tolerance coupled with more chlorophyll retention and enhanced levels of relative water content under normal/stress conditions (Singh et al, 2014; Tiwari et al, 2015). The transcription factors from Arabidopsis, AtNAC2 (Patil et al, 2014), AtDREB1A (Sarkar et al, 2014, 2016) and horsegram, MuNAC4 (Pandurangaiah et al, 2014) were exhibited drought and salt stress tolerance in groundnut by reducing the membrane damage and improving scavenging of reactive oxygen species scavenging (ROS).…”
Section: Introductionmentioning
confidence: 99%